Strategi Pemasaran Rumah Makan Wong Solo Kota Sorong Dalam Mengembangkan Usaha Perspektif Pemasaran Islam - Mira Sartika (Prodi Ekonomi Syariah IAIN Sorong, 2021)
This study discusses the marketing strategy of the Wong Solo restaurant in developing an Islamic Marketing Perspective business. The purpose of this study is to find out how the strategy of Wong Solo restaurant in developing its business and how it is viewed from an Islamic Marketing Perspective. This type of research is qualitative research, namely descriptive research. Furthermore, the data collection method in this study used observation, interviews, and documentation. The data processing and analysis techniques go through three stages, namely data reduction, data presentation, and drawing conclusions. After the authors analyzed the data, it was found that the marketing strategy of the Wong Solo Restaurant applies the 4P concept, namely: (1) product, by providing ready-to-eat food products with various types of quality food, (2) price, by setting prices. that can be reached by consumers, (3) place, providing a comfortable place and has complete facilities, (4) promotion, using various social media and consumers, namely word of mouth. Meanwhile, for marketing in an Islamic marketing perspective, by using 5 concepts of marketing values ​​in Islam, namely: (1) honest, in doing business, choosing the quality of food ingredients, how to manage and determining the price, (2) always prioritize the production process and processing that is guaranteed to be halal. and cleanliness, (3) providing public facilities that can be used at any time by consumers, (4) professionalism in serving consumers in terms of taste, facilities, and service, (5) issuing zakat, infaq, and alms.